2019
DOI: 10.1371/journal.pone.0220863
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of normal body mass index on physical fitness: A cross-sectional study among children and adolescents in Xinjiang Uyghur Autonomous Region, China

Abstract: Objective To assess the association between body mass index (BMI) and physical fitness index (PFI) among children and adolescents in Xinjiang Uyghur Autonomous Region, China. Methods In total, 17,618 children and adolescents aged 7–18 years from the selected region were enrolled in this cross-sectional study (8,800 boys and 8,818 girls). Participants were stratified by age and sex and divided into five groups by BMI percentiles: very low (BMI <5th percentile); low, (5th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
1
19
0
3
Order By: Relevance
“…We used a standing long jump to assess lower limb strength and oblique body pull-ups for boys aged 7-12, pull-ups for boys aged 13-18, and 1-min sit-ups for all girls aged 7-18, to assess upper body muscle strength. The cardiopulmonary function was assessed with long-distance running (eight 50-m shuttle runs for participants aged 7-12, 1000-m endurance running for boys aged 13-18, and 800-m endurance running for girls aged [13][14][15][16][17][18]. The 50-m dash was used to assess speed of movement.…”
Section: Procedures and Measurementmentioning
confidence: 99%
“…We used a standing long jump to assess lower limb strength and oblique body pull-ups for boys aged 7-12, pull-ups for boys aged 13-18, and 1-min sit-ups for all girls aged 7-18, to assess upper body muscle strength. The cardiopulmonary function was assessed with long-distance running (eight 50-m shuttle runs for participants aged 7-12, 1000-m endurance running for boys aged 13-18, and 800-m endurance running for girls aged [13][14][15][16][17][18]. The 50-m dash was used to assess speed of movement.…”
Section: Procedures and Measurementmentioning
confidence: 99%
“…Many studies showed that low physical activity is often positively associated with overweight [ 46 , 47 ]. A study by [ 48 ] demonstrated that BMI is significantly associated with physical activity during puberty (13–18 years) in boys and in pre-pubertal girls aged 7–12 years [ 48 ]. A study by [ 49 ], however, found that there was no significant relationship between the type of class (i.e., general education vs. sports focused).…”
Section: Discussionmentioning
confidence: 99%
“…Boys were also found to have greater physical endurance (hanging on the bar with their arms bent) of muscles (Pikel et al, 2017). Bi (2019) notes that boys are more physically fit than girls and they can show greater strength. At the age of 5, they can jump further, run faster, or drop the ball five feet further.…”
Section: Discussionmentioning
confidence: 99%